Zygomatic repositioning and Le Fort II distraction with intraoral devices in Apert syndrome: A case report. Issue 4 (April 2022) - Nørholt, Sven Erik; Sköldstam, Josephine; Blomlöf, Johan; Karunahara, Sujeeva; Pedersen, Thomas Klit
Abstract: The aim of this case report is to describe the surgical technique and outcome using internal intraoral distraction devices in LeFort II distraction with zygomatic repositioning (LF2ZR). In Apert syndrome the midface is characterized by a complex hypoplasia, with the central part being more affected than the lateral orbito-zygomatic complex. In LF2ZR, the zygomas are repositioned and internally fixated, and the central midface is further advanced through a LeFort II distraction. In previous publications, the distraction has been performed using external halo-based devices. It seems that the LF2ZR procedure can be planned and performed with adequate accuracy using virtual surgical planning tools. Knowledge about the possibility of using internal intraoral distraction devices in LF2ZR is important, as the inconspicuous placement of intraoral devices can be advantageous for some patients.